Dickens After Dickens - Bell, Emily (White Rose University Press, 2020)
"[W]e have a long way to travel before we get back to what Dickens meant... G.K. Chesterton, Charles Dickens The twentieth and twenty-first centuries have continued the quest, so aptly described by G. K. Chesterton in 1906, to 'find' Charles Dickens and recapture the characteristically Dickensian. From research attempting to classify and categorise the nature of his popularity to a century of film adaptations, Dickens's legacy encompasses an array of conventional and innovative forms. Dickens After Dickens includes chapters from rising and leading scholars in the field, offering creative and varied discussion of the continued and evolving influence of Dickens and the nature of his legacy across the 19th, 20th and 21st centuries. Its chapters show the surprising resonances that Dickens has had and continues to have, arguing that the author's impact can be seen in mainstream cultural phenomena such as HBO's TV series The Wire and Donna Tartt's novel The Goldfinch, as well as in diverse areas such as Norwegian literature, video games and neo-Victorian fiction. It discusses Dickens as a biographical figure, an intertextual moment, and a medium through which to explore contemporary concerns around gender and representation. The new research represented in this book brings together a range of methodologies, approaches and sources, offering an accessible and engaging re-evaluation that will be of interest to scholars of Dickens, Victorian fiction, adaptation, and cultural history, and to teachers, students, and general readers interested in the ways in which we continue to read and be influenced by the author's work. This collection is edited by Dr Emily Bell (Loughborough University) with a Foreword by Professor Juliet John (Royal Holloway, University of London), author of Dickens and Mass Culture (OUP). Dr Bell is a board member for the Oxford Dickens series and an editor for the Dickens Letters Project. She also acted as the first Communications Committee Chair of the international Dickens Society, and has published on Dickens, life writing and commemoration. "